Pick Your Own Learning (PYOL) as a Differentiated Pedagogical Intervention to Foster Self-Regulation and Metacognitive Awareness in EFL Learning - Fidelis Averina; Alberik Ryan Tendy Wijaya (Prodi Pendidikan Bahasa Inggris, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Islam Darul Ulum Lamongan*, 2026)
The study of self-regulated learning has been ubiquitously conducted in the scope of language learning; however, very few of them explore the role of differentiated instructions in fostering self-regulated learning and metacognition in the EFL context. Thus, the present study aimed to examine the implementation of differentiated, student-selected learning activities through the Pick Your Own Learning (PYOL) assignment in an English Integrated Course, a compulsory first-semester course, the benefits that they gained in the process, and to identify challenges that may hinder the development of these capacities. To achieve the aforementioned aim, a mixed-method research design was employed involving 18 EFL students enrolling in a course at one of the private universities in Surabaya. In addition, students’ weekly reflections and learning artifacts were analyzed to ensure triangulation. The findings suggested that PYOL, as differentiated instruction, could serve as a medium to promote learner autonomy, motivation, and active engagement, while also supporting the development of metacognitive awareness and self-regulatory behaviors. In addition, students perceived meaningful benefits in terms of language development, creative expression, and ownership of learning. However, these benefits were accompanied by challenges, particularly in time management, goal setting, topic selection, and linguistic limitations. The findings imply that EFL teachers should support differentiated and student-selected learning activities through structured autonomy rather than simply giving students freedom of choice. In implementing PYOL, teachers need to provide clear guidance, planning support, progress monitoring, and reflection so that students can make purposeful choices and gradually become more independent learners.